The Impact of Psychological Warfare in the Palestinian Media on Israeli Society "The July War 2014 as a model" - Thuraya, Mohammed Saeed (Journal of Humanities & Social Sciences, 2021)
The study aimed to know the role of psychological warfare in the Palestinian media on Israeli society during the 2014 war, and the researcher used the descriptive and analytical approach, whereby the researcher used the interview tool with political analysts, media professionals, and specialists in Israeli affairs, psychology and the media, who numbered 25 personalities, to find out how it affected The psychological war in the Palestinian media on the Israeli occupation society. The study concluded that the success of the Palestinian media in reaching the Israeli society and communicating its voice, as well as the success of the Palestinian media in affecting the morale of the Israeli occupation society. The study recommended the establishment of radio, satellite channels, and websites in the Hebrew language aimed at the Israeli public and based in its programs on the media strategy, in addition to establishing a unified media strategy for all Palestinian media, and working to reach the largest segment of Israeli society through the Palestinian media.